Effect of school social climate on life satisfaction of primary and secondary education students - Leria-Dulčić, Francisco Jose (2018)
Perception of school social climateas well as the degree of satisfaction with life and students’ surroundings are currently getting a major  interest from the scientific community, within the framework of the permanent concern for school coexistence and the individual and social variables that participate in it. To contribute to this purpose, the perceived School Social Climate and the Total Life Satisfaction of 479 primary and secondary students were evaluated through the Multidimensional Student Satisfaction Scales (MSLSS); Student Life Satisfaction (SLSS); School Social Climate (ECLIS), and a sociodemographic survey. Through a cross-curricular associative-comparative strategy and a design of natural groups, it was found that Total Life Satisfaction was predicted mainly by the School Climate perceived around the School and the peers. The Vital Satisfaction dimensions most explained by the predicting variables were those related to school (37.3%), friends (20.9%), and total life satisfaction (33.2%); indicating the relevance of the school context for students’ satisfaction with their educational environment, especially the peer group. The implications of the findings for future studies are discussed, as well as the public educational policies on school coexistence.